Cultural Understanding and Language Translation (Journal of Human Sciences, 2020)
Language, being an exclusively human feature, is principally dynamic; it involves a diversity of changes and adjustments in its course of existence. It is also considered as a factor that links distinct cultures and a way of expressing thoughts and feelings; accordingly, translation is one of the principal, ultimate and appropriate ways in transferring culture. Translation, including the transposition of thoughts expressed in one language by a specific social community into the adequate expression of another social community. As cultures are increasingly brought into greater contact with one another, multicultural concessions and considerations are taken to an increasing degree and as a result, the process of cultural translation takes place. As a result, our broad discussion topic in language is not the relationship between translation and culture since there is an close relationship between translation and culture. What interests us in the present paper is not accomplishing only a particular defined ideal equivalence relation between translation and culture, but, among other things, how do some precise changes influence us when we are trying to comprehend a text before finally translating it? We are not just dealing with words in a written form in a specific period of time, situation and place; most significantly it is the "cultural" aspect of the source text that we must take into account. The process of transfer across cultures, should; consequently, communicate the aspect with regard to the target culture to ensure consistency in the eyes of the target reader.